Continuous Fermi level tuning of Nb-doped WSe2 under an external electric field. (22nd December 2021) - Hisama, Kaoru; Gao, Yanlin; Maruyama, Mina; Kitaura, Ryo; Okada, Susumu
Abstract: The possibility of continuous Fermi level tuning of Nb-doped WSe2 under an external electric field is investigated, using the density functional theory combined with the effective screening medium method. The Fermi level monotonically increases and decreases as the carrier concentration increases and decreases, respectively, by controlling the external electric field. The electronic structure of Nb-doped WSe2 is insensitive to the Nb concentration and arrangement. Furthermore, it was demonstrated that the electric field simply shifts the Fermi level of Nb-doped WSe2, resulting in the constant quantum capacitance through the gate voltage, irrespective of the Nb concentration and arrangement.